Comparison between open reduction and internal fixation and minimally invasive surgery in management of Sanders type II calcaneal fracture: A randomized controlled trial protocol - Xue, Dingshan (Medicine (Baltimore), 2020)
BACKGROUND: The minimally invasive surgery possesses an essential and growing function in treating the calcaneal fractures, but the related literature on this topic is limited. For our study, the main purpose was to compare the early prognosis of a group of the patients with Sanders type II fracture of calcaneus treated via minimally invasive surgery and open reduction and internal fixation (ORIF). METHODS: This is a prospective randomized controlled trial in the patients who suffer from displaced intra-articular calcaneal fractures. This current study was carried out in accordance with the guidelines of “CONSORT statement” for the randomized controlled studies. All patients were randomly assigned into 2 groups on the basis of a random number table, namely the minimally invasive treatment group and the ORIF group using conventional methods. Inclusion criteria included the followings: aged between 18 to 59 years old; closed and unilateral fracture; patients with displaced intra-articular calcaneal fracture (>2 mm) involving Sanders Type IIC and Type IIB; and patients have enough mental capacity to understand and answer questions in the evaluation scale. In the process of outpatient follow-up, the radiographs were taken at 1, 3, 6, and 12 months. The functional results involved the American Orthopaedic Foot and Ankle Score, Foot Function Index, and the pain score. CONCLUSIONS: This protocol will give us research directions in future work. TRIAL REGISTRATION: This study protocol was registered in Research Registry (researchregistry6261).